A compact omnidirectional dual‐circinal rectenna for 2.45 GHz wireless power transfer. Issue 1 (3rd December 2018) - Wang, Meng; Yang, Lan; Fan, Yue; Shen, Minghui; Li, Yan; Shi, Yanyan
Abstract: A compact dual‐circinal rectenna with omnidirectional characteristic is designed for microwave wireless power transmission at 2.45 GHz. A novel dual‐circinal receiving antenna with the reflection coefficient of −32.5 dB is proposed which is formed by expanding folded curves. By designing an impedance matching network with a 60 ° radial stub and a single stub, a rectifier is presented with the maximum efficiency of 55.6 % and the output dc voltage of 1.19 V under the input power of 0 dBm. Simulation and measurements have been carried out for the antenna and the rectifier. The measured results agree well with the simulated value. The results of rectenna experiment show that the maximum conversion efficiency is 51% at 2.45 GHz when the input power is 0 dBm. The proposed rectenna has the characteristics of compact size and omnidirectional harvesting which are advantageous in RF energy harvesting applications.